RANCANG BANGUN APLIKASI PERSEDIAAN KAIN BERBASIS WEBDENGAN METODE REORDER POINT (ROP) DI DEPARTEMEN KREATIF PT. INDO PACIFIC - COMPUTING INFORMATIKA; yusuf Muharam; Rustiyana (Program Studi Teknik Informatika FTI UNIBBA, 2023)
: PT. Indo Pacific is a private company operating in the textile sector, where in the creative department of PT. Indo Pacific requires inventory data on goods allocated for fabric inventory which is useful for controlling the company's existing fabric inventory. The inventory system in a company plays an important role because inventory can simplify or expedite work in managing stock data. The data collection system in the creative department still uses handwriting so that the data reports presented are very ineffective and require quite a long time to complete, and there is often a buildup and reduction in stock of fabric that runs out and is not known to employees. Therefore, we need a web-based data processing application with the Reorder Point method which is expected to facilitate fabric data collection in the creative department. And this application was built using the Reorder Point (ROP) method with a feature of displaying stock quantities less than 10 meters or yards which functions to prevent shortages of fabric which could cause delays in fulfilling customer requests. designing an application using UML (Unified Modeling Language) and research methods using the SDLC waterfall method. The final result of this research is the development of a fabric inventory data collection application in the creative department of PT. Indo Pacific.